Digital media consumption: Using metrics, patterns and dashboards to enhance data‐driven decision‐making. Issue 1 (25th November 2021) - Chan, Kaye; Uncles, Mark
Abstract: Dashboards are commonly used to inform data‐driven decision‐making by multiple stakeholders within and across businesses. The purpose of this article is to show how a comprehensive marketing model, the NBD‐Dirichlet, can be used to construct coherent and integrated dashboards. This is demonstrated using an example that offers practical guidance to practitioners and researchers for incorporating the model into a dashboard and showing how it can enhance visualisation, communication, and decision‐making. The example concerns digital media consumption behaviour, specifically the section choice behaviour of readers of an online magazine. The example demonstrates the utility of the NBD‐Dirichlet model to underpin a marketing management dashboard (RQ1), where model parameters are estimated from unstructured log‐file data (RQ2) using log‐likelihood estimation (RQ4). The example also shows the applicability of the model in analysing a non‐brand attribute, specifically magazine content sections (RQ3). From inspection of graphical and tabular dashboards, it is evident that magazine section content is read by consumers in ways we might expect given the well‐known Double Jeopardy (DJ) pattern of the NBD‐Dirichlet model (RQ5). There is no evidence of change‐of‐pace behavioural loyalty (RQ6), nor niche behavioural loyalty (RQ7). Finally, the article highlights the benefits of the NBD‐Dirichlet in business as not only a tool for underpinning dashboards but also for scenario planning (RQ8).